Vegetable Production Potential and Income Generation in Barmer District (Current Horticulture, 2024)
The study conducted in Barmer district, Rajasthan, revealed that the region offers favorable conditions for the cultivation of arid  vegetables despite various bio-physical constraints. Barmer district is situated between 24°40’00” and 26°32’00” North latitudes  and 70°05’00” and 72°52’00” East longitudes, covering a geographical area of 28,387 km². Despite various biophysical constraints,  Barmer district offers very good opportunities for cultivation of arid vegetables like mateera (Citrullus lanatus), snapmelon  (Cucumis melo), kachari, brinjal (Solanum melongena), bottle gourds (Lagenaria siceraria), round melon (Praecitrullus fistulosus),  Indian aloe (Aloe barbadensis), and Khejri sangari (green pods of Prosopis cineraria). The authentic data about the present situation,  production potential, and problems are not available. To determine the production and yield potential, income generation, and  profits, it is essential to know the vegetables grown during the Kharif and Rabi seasons to make suitable plans and strategies to  encourage their production in the hot/hostile arid environment. Keeping that in view, the present study aimed to gather data on  the current situation, production potential, problems, and income generation in order to develop suitable plans and strategies  for encouraging vegetable production in the hot and hostile arid environment.
Keywords: bean; Vegetable; Generation; Potential